Optimal allocation of distributed generation and reactive power in simplified distribution systems - Salas, Richard Wilcamango [UNESP]; Melgar-Dominguez, Ozy D. [UNESP]; Mantovani, Jose R. S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
This work presents a novel strategy to solve a short-term planning problem for electrical distribution systems (EDSs) by taking advantage of the implementation of a simplification technique. This simplification technique removes nodes and circuits from the original EDS to reduce the number of variables to be considered in the planning stage. The planning problem is formulated as a mixed-integer linear programming problem and its solution determines the optimal allocation of capacitor banks (CBs) and wind-based distributed generation (DG) units. To validate the proposed strategy, three different test cases are analyzed using a 134-node system and its respective simplified 23-node EDS. Numerical results show that similar investment plans for the both systems can be obtained.
Keywords: Capacitor banks; Distributed generation; Electric distribution system planning; Simplification technique